PWE-118 Mdm2 expression in the progression of barrett's oesophagus. (17th June 2017) - Robinson, L; Abradu-Berchie, B; Ilyas, M; Ragunath, K; Card, T; Kaye, P
Abstract : Introduction: Background: Barrett's Oesophagus (BO) is the leading pathological risk factor for oesophageal adenocarcinoma (OAC), a cancer rapidly increasing in the western world. The histological diagnosis of dysplasia is used to determine this risk in BO patients; p53 immunostaining is used as an additional marker. There is a need for less subjective, low-risk markers. MDM2 is an essential negative regulator of p53. MDM2 has been found to be regulated by p53 and also to have p53-independent functions. This study aimed to assess the expression of MDM2 in the progression of BO, how it varies with p53 expression and if MDM2 expression in early stages may predict progression to OAC. Method: Methods: BO cases with ND, ID, LGD that progressed or didn't progress to high-grade dysplasia (HGD)/OAC as well as a sample of HGD and OAC cases were stained immunohistochemically for MDM2. The slides were scored and assessed with p53 and H and E slides of the same cases. Relationship with MDM2 expression was evaluated in the increasing grades of dysplasia and correlated with p53 expression and related to progression. Results: Results: There was a statistically significant positive correlation (Spearman's rho value=0.47, p<0.001) with increasing MDM2 staining intensity as the grades of dysplasia increased. MDM2 expression had no significant predictive effect on progression to HGD/OAC. A statistically significant 62% of p53 cases with significant staining (positive or absent) had strong MDM2 staining (Fishers exact test: p=0.022). Conclusion: Conclusion: Increased MDM2 expression was observed more frequently with higher grades of dysplasia, alongside abnormal p53 expression. This study supports the possibility of mutant p53 stabilising MDM2 and the p53-independent effects of MDM2. Clinically, it appears that MDM2 is not a useful risk marker for predicting progression to OAC. Future research should continue investigating markers to help predict progression of BO to OAC. Disclosure of Interest: None Declared